2021
DOI: 10.1186/s12913-021-07367-3
|View full text |Cite
|
Sign up to set email alerts
|

Underlying factors and challenges of implementing the urban family physician program in Iran

Abstract: Background The family physician program was launched in 2005 in rural areas of Iran and then piloted in 2012 in the cities of Fars and Mazandaran provinces due to insufficient health coverage in these cities. However, despite its pivotal role in the health system, this program has not progressed according to the policies. This study aimed to explain the underlying factors and challenges of implementing the urban family physician program in Iran. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Since the initiation of FPP in Iran, many studies and reports (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) have provided some lines of evidence that show a variety of challenges in the educational system of FPs in Iran. As this program is going to be expanded across the country, this systematic review of the literature was performed to provide a comprehensive view of the existing challenges associated with the education of family physicians in Iran. This current review of the literature identified consistent themes associated with the educational system and challenges encountered in preparing physicians for FPP upon graduation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initiation of FPP in Iran, many studies and reports (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) have provided some lines of evidence that show a variety of challenges in the educational system of FPs in Iran. As this program is going to be expanded across the country, this systematic review of the literature was performed to provide a comprehensive view of the existing challenges associated with the education of family physicians in Iran. This current review of the literature identified consistent themes associated with the educational system and challenges encountered in preparing physicians for FPP upon graduation.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment-oriented approach in medical schools does not include meaningful training for the individual health-promotion and prevention-oriented approach of FPP. Training in public health was also minimal (6,8,(10)(11)(12)(13)(14). The current hospital-centered model focuses on complicated diseases.…”
Section: Educational Systemmentioning
confidence: 99%
“…One of the most critical reforms in the health system is the service-leveling method. The family physician provides prevention and treatment services at the first level, directs patients to specialized levels, and pursues the results, if necessary (4,5). The achievements of the family physician program have led the World Health Organization (WHO) to designate it as the center of global efforts to improve quality, effectiveness, equity, and reduce costs in the health care system (6).…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas, the physicians' duties in the health team are defined as health management, population health care and appropriate referral measures, implementation of empowerment programs based on local capacity, and monitoring the performance of the health team (9). Previous studies stated that increasing work-load, quantity, and quality of medical facilities in the workplace are the most critical problems of physicians (4). On the other hand, it has resulted in family physicians' insufficient knowledge and skills compared to the health system's expectations (13).…”
Section: Introductionmentioning
confidence: 99%
“…All cities with a population of over fifty thousand have at least one public hospital, whereas almost all private hospitals are located in provincial capitals [ 7 ]. Lastly, In Iran’s health system, due to the lack of a mandatory referral system, people can choose the service provider, the level of specialization, and the geographical location to receive the service [ 13 ].…”
Section: Introductionmentioning
confidence: 99%